The Revival Of The Teaching Of Folk Epics In The Years Of Independence and Its Significance - Anisbekova Dilfuza Makhammadumar Kizi (Indonesian Journal Publisher, 2025)
With the declaration of independence, a new approach to the history of the Uzbek people became possible. Research on the cultural and spiritual heritage of past eras will serve the spiritual development and enrichment of peoples, the formation of a new spirituality. This article explores the heroic work carried out by scientists and thinkers on the restoration of the teaching of folk epics in our independent country and the stages of its development, the restoration and preparation of folk epics as an object of study. The main purpose of the article includes the theoretical analysis of scientific views on the theoretical methodological foundations of the teaching of folk epics, expressed by research scientists. In the study, the principles of historicism, continuity and logic were studied on the basis of modern approaches. The result is an analysis of the foundations of achievements in the field of folk oral creativity of fiction after the independence period